Exploring the Integration of Indigenous Healing and Western Psychotherapy for Sexual Trauma Survivors Who Use Mental Health Services at Anishnawbe Health Toronto - Reeves, Allison; Stewart, Suzanne L. (Canadian Journal of Counselling and Psychotherapy, 2014)
Sexual traumas, including sexual abuse and sexualized violence, remain substantially higher among Indigenous peoples in Canada than among non-Indigenous peoples. These trends are rooted in a colonial history that includes a deprivation of lands and culture, residential schooling, and other intergenerational traumas. Mental health sequelae following sexual traumas such as abuse and violence may include mood disorders, low self-worth, posttraumatic stress, and a range of issues related to anxiety. Perhaps unsurprisingly, Western mental health services are typically underutilized by Indigenous peoples managing these issues. This article details a qualitative, community-based project undertaken in partnership with Anishnawbe Health Toronto that explores how Indigenous healing in the Anishnawbe tradition, alongside Western therapy services, can improve the mental health of Indigenous clients who have experienced sexual trauma. Findings detail themes related to loss and recovery from an Indigenous standpoint and emphasize the need for trauma-informed care, alongside culture-informed care, in order to meet the holistic mental health needs of these clients. The inclusion of traditional healing services offers a culturally appropriate pathway to recovery for Indigenous clients who are sexual trauma survivors.